2016
DOI: 10.25008/jkiski.v1i2.53
|View full text |Cite
|
Sign up to set email alerts
|

Perspektif Triplehelix Dalam Nation Brand Indonesia

Abstract: AbstrakMomentum memperkuat nation brand Indonesia semakin tinggi seiring dengan penguatan sistem pemerintahan yang demokratis dan eksplorasi keberagaman kultur. Namun persepsi negatif masih muncul dan Indonesia belum memiliki reputasi yang baik di mata masyarakat dari negara lain. Oleh karena itu dengan pendekatan grounded theory berbasis wawancara mendalam, konsep triple helix yang memadukan aspek pemerintah, bisnis, dan masyarakat sipil digali dan dianalisis secara tematik. Hasil temuan memperlihatkan, persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The study also In a previous study titled 'Triple Helix Perspective in Indonesia's Nation Brand,' the author found that the Triple Helix perspective in nation branding can be considered a crucial and inseparable force. This research also demonstrates that the quality of integrated service systems, bureaucratic reforms, mental revolutions, synchronization across sectors and regulations, human resource quality, work culture, infrastructure, facilities, national values, and philosophical principles, packaging, and product resilience are strengtheners and complements to Indonesia's hospitality in building a nation brand (Irwansyah, 2016). The Triple Helix nation branding referred to in this research is a dimension that provides various perspectives on Indonesia, comprising the government, business, and civil society.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The study also In a previous study titled 'Triple Helix Perspective in Indonesia's Nation Brand,' the author found that the Triple Helix perspective in nation branding can be considered a crucial and inseparable force. This research also demonstrates that the quality of integrated service systems, bureaucratic reforms, mental revolutions, synchronization across sectors and regulations, human resource quality, work culture, infrastructure, facilities, national values, and philosophical principles, packaging, and product resilience are strengtheners and complements to Indonesia's hospitality in building a nation brand (Irwansyah, 2016). The Triple Helix nation branding referred to in this research is a dimension that provides various perspectives on Indonesia, comprising the government, business, and civil society.…”
Section: Introductionmentioning
confidence: 77%
“…To build a strong brand, the depiction must be consistent, memorable, and distinguishable from other nations. Lindstrom (in (Irwansyah, 2016)) states that a robust nation brand not only has positive impacts on tourism and business but also creates a comprehensive branding ecosystem for the country.…”
Section: Brand Equalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Jika persepsi melekat dalam waktu lama, akan membentuk citra. Logo instansi selalu memiliki nilai simbolik secara individu yang didasarkan pada konsistensi kinerja institusi (Rustan, 2013, Irwansyah, 2016.…”
Section: Hasil Penelitianunclassified